Implementation Of Mobile-Based OOAD Interactive Learning Media - I Nyoman Tri Anindia Putra; Ketut Sepdyana Kartini; Komang Redy Winatha (Jurusan Teknik Informatika, 2022)
The lack of interest in student learning is due to the learning media used are less attractive and effective to understand the material. This study aims to implement mobile-based interactive learning media regarding OOAD material. The media feasibility test uses a blackbox testing scenario and the analysis uses the Gutman scale technique. From the test results, it was found that the percentage of blackbox testing was 100% and the functional requirements test by the resource persons obtained a percentage of 100%. Based on the results of these studies, it can be explained that this learning media is very good and has been feasible to be implemented.